Research on Screw Propulsion Performance of Amphibious Robot - Pengfei XU; Zipeng WANG; Hailong LIN; Yan KAI; Qiao HU; Jianye SU (水下无人系统学报)
The traditional amphibious locomotion mode mainly features the dual system of wheel or track combined with a propeller. In contrast, single-system amphibious locomotion mode has become a research hotspot in recent years because of its low system complexity and high efficiency. As a single-system amphibious locomotion mode, screw propulsion has good adaptability in semi-fluid environments such as swamp and mud flat. Over the years, there have been many research designs on its driving on land, but few studies on its driving in water. In this paper, the underwater performance of the screw propulsion device was studied, and the design method of the screw cylinder was proposed according to the principle of screw propulsion. The hydrodynamic simulation method was used to calculate the thrust of the screw cylinder at different submerged depths, and it was found that the thrust generated by the screw cylinder was the largest at 0.9 times the submerged depth. Based on the self-designed and developed amphibious robot prototype, the underwater propulsion test was carried out, and the results show that the underwater screw cylinder propulsion state is stable. In addition, the response surface method is used to optimize the design of the screw cylinder from the two aspects of screw blade height and pitch, and the optimization results can increase the propulsion efficiency by 18.2% compared with the original design scheme.